Mediasi Pembagian Harta Bersama dalam Putusan Pengadilan Agama Sleman Nomor 413/Pdt.G/2015/PA. Smn - Suprianto, Agus (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
According to the Civil Code and KHI, the settlement of joint assets is divided by half for widows and widowers respectively. Absolute competence for dispute resolution in the Religious Courts. The study of the decision on the joint property dispute is based on the success through the peace agreement of Case No. 413/Pdt.G/2015/PA. Smn at the Sleman Religious Court. In conclusion, the verdict reads: “states that there has been a reconciliation between the Plaintiff and the Defendant. Punish the Plaintiff and Defendant to comply with the contents of the peace. The peace agreement is to end the dispute, the peace decision is binding on the parties and related parties, the peace decision is executorial, the mediation process proves as an alternative form of fast dispute resolution, the peace decision has a sense of substantive justice, mediation reflects the good faith behavior of the parties, mediation prioritizes the negotiation process, a written peace agreement that is documented and signed, the peace agreement is strengthened by a court decision, the peace agreement reduces the negative impact on children after divorce and improves friendship, and peace is relevant to the provisions of the Qur'an and hadith.